Response of chickpea (Cicer arietinum) to molybdenum in moderately-alkaline soil - VENKATESH, M S; HAZRA, K K; GHOSH, P K; SINGH, S S; CHATURVEDI, S K (The Indian Journal of Agricultural Sciences, 2020)
A pot experiment was conducted at ICAR-Indian Institute of Pulses Research, Kanpur during 2010–12 to assess the response of chickpea crop to molybdenum (Mo) in moderately-alkaline Inceptisol (pH 8.0-8.1). Soil application of Mo at 1 kg/ha increased the grain yield by 7.8–11.9% (P< 0.05). However, the Mo seed treatment (4 g/kg seed) had a marginal and mostly non-significant effect on growth and yield attributes of chickpea. The higher aboveground dry matter (10.0–19.3%), root weight (11.6–12.5%), nodule weight (7.1–12.1%), and pod number per plant (11.8–22.0%) were observed with soil application of Mo over control treatment. Notably, a negative interaction (P<0.05) between phosphorus and Mo was noticed for aboveground growth of chickpea.Thus, Mo was observed as a limiting nutrient for chickpea in moderately-alkaline soil and application of Mo at 1 kg/ha to soil may be recommended to harvest the potential productivity of chickpea.